Oxidant-free cross-dehydrogenative oxyalkylation enables late-stage functionalization of drugs - Weiqiu Liang; Jiahao Li; Jianbin Li; Chengda Wu; Zhiyu Tu; Bo-Shuai Mu; Yang Xu; Longlong Song; Mengxin Xu; Xi-Yang Cui; Chao-Jun Li; Zhibo Liu (The Innovation)
Late-stage functionalization is an attractive strategy that allows chemists to bypass lengthy synthetic processes, facilitating the rapid generation of drug analogs with potentially enhanced pharmacokinetic and pharmacological properties. This study describes a novel approach for cross-dehydrogenative oxyalkylation, leveraging a unique γ-ray-enabled photoredox process to generate oxyalkyl radicals, followed by a Minisci-type addition in an aqueous solution. The metal- and oxidant-free aqueous conditions, coupled with excellent functional group compatibility, establish this method as a versatile protocol for the late-stage oxyalkylation of unprotected, structurally complex drug molecules. Notably, this method demonstrated improved pharmacokinetics in hydroxymethylated fibroblast activation protein inhibitor (FAPI) molecules, highlighting its potential to accelerate drug discovery efforts.